SPIDER-1 measurements (LP, GPS, SMILE) inside an aurora - Giono, Gabriel; Ivchenko, Nickolay (Swedish National Data Service, 2021)
A series of CSV files containing some of the measurements performed by the SPIDER-1 sounding rocket inside an aurora. The rocket was launched at 21:09UT on February 2nd 2016 from Esrange (Kiruna, Sweden) and ejected 10 Free Falling Units (FFUs) inside a westward-traveling active aurora. Each FFU was equipped with a deployable Langmuir probe (LP) to measure the plasma properties (the electron density ne, the electron temperature Te, and the plasma potential Vp), as well as a 3-axis fluxgate magnetometer (SMILE) measuring the magnetic field and a positioning recorder (GPS). Usable data from two of the FFUs (FFU02 and FFU06) is presented, which was used in the JGR-Space Physics article named "Multi-point measurements of the plasma properties inside an aurora from the SPIDER sounding rocket." The data was collected by two of the SPIDER Free Falling Units (FFU02 and FFU06). It included: - Measurements from the Langmuir probe (LP, current measurements for each voltage bias steps) - Measurements from the 3-axis magnetometer (SMILE) - Processed data from the Langmuir probe, namely the electron density (ne), electron temperature (Te) and plasma potential (Vp). - GPS position of the two FFUs. En serie CSV-filer som innehåller en del av mätningen utförd av SPIDER-1 raket. Raketen lanserades kl.21: 09UT den 2 februari 2016 från Esrange (Kiruna, Sverige) och kastades ut 10 Free Falling Units (FFUs) inuti en västerutgående aurora. Varje FFU var utrustad med en utvecklingsbar Langmuir-sond (LP) för att mäta plasmagenskaperna (elektrontätheten ne, elektrontemperaturen Te och plasmapotentialen Vp), samt en 3-axlig fluxgate magnetometer (SMILE) som mäter den magnetiska fält och en positioneringsutrustning (GPS). Användbara data från två FFU (FFU02 och FFU06) presenteras, vilket användes i JGR-Space Physics-artikeln med namnet "Multi-point measurements of the plasma properties inside an aurora from the SPIDER sounding rocket." Uppgifterna samlades in av två av SPIDER Free Falling Units (FFU02 och FFU06). De inkluderar: - ...